The power of power politics : from classical realism to neotraditionalism - Vasquez, John A., 1945- (Cambridge studies in international relations, 1998)
In this new and much-expanded edition of his classic study, John Vasquez examines the power of the power politics perspective to dominate inquiry, and evaluates its ability to provide accurate explanations of the fundamental forces underlying world politics.